Electroactive polyurea/CNT composite-based electrode for detection of vitamin C - T. C. Huang (eXPRESS Polymer Letters, 2016)
The electrocatalytic oxidation of vitamin C at carbon paste electrode (CPE) modified with amino-functionalized multiwalled carbon nanotube/electroactive polyurea (AF-MWCNT/EPU) composite was investigated. We have synthesized novel electroactive polyurea composites containing MWCNTs functionalized with 4-aminobenzoyl groups by an oxidative coupling polymerization. Ultraviolet-Visible spectra and cyclic voltammetry studies confirmed the occurrence of efficient interaction between AF-MWCNT and EPU graft. Moreover, the electrocatalytic activity of vitamin C oxidation by utilizing aniline containing composites was evaluated, showing that the intrinsic electroactivity of AF-MWCNT/EPU-CPE had great potential application for detection of vitamin C. The detection limit and sensitivity of this sensor was 1.2 μM and 35.3 μA•mM–1, respectively.